Efeitos da combinação de antimicrobianos e inibidores de bomba de efluxo na morfologia e expressão gênica em Mycobacterium tuberculosis - Ferracioli, Katiany Rizzieri Caleffi (2014)
This work aimed in a first moment to propose an assay to easily evaluate drug combination action against Mycobacterium tuberculosis (Mtb) and second, evaluate the effects of rifampicin (RIF), isoniazid (INH) and ethambutol (EMB) with efflux pump inhibitors (EPIs), the morphology and transcriptional profile of genes encoding efflux pumps (EPs) in Mtb H37Rv exposed to specific drug combination. The results are presented in two articles: combination in Mtb H37Rv "Fast detection of drug interaction in Mycobacterium tuberculosis by the checkerboard resazurin method" and "Morphological changes and efflux pump genes differentially expressed in Mycobacterium tuberculosis exposed to rifampicin and verapamil combination." At first article, Resazurin combination drugs microtiter assay (REDCA) was proposed to evaluate the drug synergism in Mtb using as model the INH or EMB with levofloxacin drugs combination. The results were promising for levofloxacin and EMB combination, which turn it a therapeutic option to reduce EMB adverse effects. The second article evaluated the in vitro activity of individual RIF, INH, EMB and EPIs (verapamil (VP) and carbonyl cyanide m-chlorophenyl-hydrazone) by Resazurin Microtiter Plate Assay (REMA) and the combinations of anti-tuberculosis drugs with EPI by REDCA in Mtb H37Rv. EPs inhibition was assessed by the accumulation of ethidium bromide assay. The growth, morphology and expression of genes encoding for EPs were evaluated for RIF+VP combination that had the lowest fractional inhibitory concentration index by REDCA. In the bacterial time kill curve assay, a viable cell count after exposure to RIF+VP combination was similar to RIF assay. Wrinkled and rounding cells were the main morphological changes observed by scanning electron microscopy after RIF and VP exposure, respectively. The effects of RIF+VP combination appeared to be a summation of the above mentioned changes. Overexpression of some EP genes to RIF and decrease to RIF+VP, after 72 h of exposure, was observed by Real-time PCR. The present study demonstrated that the best drug combination effect in Mtb H37Rv occurred with RIF+VP, which suggest it to provide advantages over the individual RIF that compose the conventional therapy for tuberculosis, including a decrease in resistance mediated by EPs.